Biotransformation of the mineralocorticoid receptor antagonists spironolactone and canrenone by human CYP11B1 and CYP11B2: Characterization of the products and their influence on mineralocorticoid receptor transactivation. Issue 163 (October 2016) - Schiffer, Lina; Müller, Anne-Rose; Hobler, Anna; Brixius-Anderko, Simone; Zapp, Josef; Hannemann, Frank; Bernhardt, Rita
Highlights: Human CYP11B1 and CYP11B2 are shown to convert spironolactone and canrenone. Metabolites are identified by NMR as 11β-, 18- and 19-hydroxylated derivatives. Metabolism alters the antagonistic effects on the mineralocorticoid receptor. Consideration of CYP11B1 and CYP11B2 as drug-metabolizers is conclusively suggested. Abstract: Spironolactone and its major metabolite canrenone are potent mineralocorticoid receptor antagonists and are, therefore, applied as drugs for the treatment of primary aldosteronism and essential hypertension. We report that both compounds can be converted by the purified adrenocortical cytochromes P450 CYP11B1 and CYP11B2, while no conversion of the selective mineralocorticoid receptor antagonist eplerenone was observed. As their natural function, CYP11B1 and CYP11B2 carry out the final steps in the biosynthesis of gluco- and mineralocorticoids. Dissociation constants for the new exogenous substrates were determined by a spectroscopic binding assay and demonstrated to be comparable to those of the natural substrates, 11-deoxycortisol and 11-deoxycorticosterone. Metabolites were produced at preparative scale with a CYP11B2-dependent Escherichia coli whole-cell system and purified by HPLC. Using NMR spectroscopy, the metabolites of spironolactone were identified as 11β-OH-spironolactone, 18-OH-spironolactone and 19-OH-spironolactone. Canrenone was converted to 11β-OH-canrenone, 18-OH-canrenone as well as to the CYP11B2-specific product 11β, 18-diOH-canrenone. Therefore, a contribution of CYP11B1 and CYP11B2 to the biotransformation of drugs should be taken into account and the metabolites should be tested for their potential toxic and pharmacological effects. A mineralocorticoid receptor transactivation assay in antagonist mode revealed 11β-OH-spironolactone as pharmaceutically active metabolite, whereas all other hydroxylation products negate the antagonist properties of spironolactone and canrenone. Thus, human CYP11B1 and CYP11B2 turned out to metabolize steroid-based drugs additionally to the liver-dependent biotransformation of drugs. Compared with the action of the parental drug, changed properties of the metabolites at the target site have been observed.